Srpski - Kvastek, Aleksandar (Glasnik Advokatske komore Vojvodine, 2020)
In this paper is analysed the position of the injured party in the investigation conducted by the public prosecutor which is implemented in the Republic of Serbia in 2011. After we have given the definitions of the injured party and the difference with the victim, as a criminological category, we have discussed did the Serbian Code of Criminal Procedure (2011) make a step back when it comes to the position of the injured party in criminal proceedings. First of all, subsidary indictment was reduced as it is now prescribed that the injured party can overtake the criminal prosecution only after the confirmation of public prosecutor’s indictment, so the opportunity to act as a subsidary prosecutor does not exist like in the Code of Criminal Procedure of Socialist Republic of Yugoslavia from 2001. After that, we pointed out that the position of the injured party was exacerbated in the field of conditionally deffered prosecution, as a part of the principle of opportunity of prosecution, because injured party can not object to the higher public prosecutor to re-examine the decision not to prosecute and the injured party’s consent is not needed for this decision. The research we have carried out with the deputy public prosecutors and attorneys at law confirmed our presumptions that the actual Code of Criminal Procedure downgraded the injured party’s impact on the criminal proceedings.